A política de expansão das universidades federais e os seus efeitos sobre indicadores municipais - Casqueiro, Mayara Lima (2017)
In the light of the expansion of the higher education network, the propose od this study is to analyze the impact of Federal Universities expansion on Brazilian cities development based on economic, social and labor market indicators. In addition to his, it was sought to identify the factors that influenced the municipalities to be contemplated with a university campus. Moreover, the propensity score matching method was used to construct a control group that most closely resembled a treatment group. And, to estimate the effects, after the pairing, the Differences in Differences and Fixed Effect estimators were used. The results indicate that municipalities with a private university campus, population of more than 50,000 inhabitants and with greater economic relevance (importance of GDP) in their micro-region are factors (or characteristics) that influenced the choice of municipalities benefited by the expansion policy. Regarding the effects of the expansion on the indicators, it is observed that the creation of new campuses reduces the percentage of poverty in the municipalities, on average, by 1.5 pp. In addition, there is (weak) evidence that the policy increases the income per capita, the percentage of employed people with higher and medium levels. However, it should be noted that a longer period of time may be required for the effects of the expansion policy to have significant impacts on the economy.